2011
DOI: 10.1177/000313481107700120
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Giant Hepatic Hemangiomas: Technical Point of View

Abstract: Hepatic hemangiomas are the most common benign tumors of the liver. Surgical treatment can be difficult as a result of the high risk of intraoperative hemorrhage. The present study reviewed clinical features of patients with hepatic hemangioma and surgical techniques used in their treatment. Eight patients with giant hepatic hemangiomas underwent hepatectomies at the Asan Medial Center between January 2006 and March 2009. Patient demographic, clinical, and surgical characteristics and outcomes were reviewed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…6 Hemangiomas are usually seen between the ages of 30-50 years, with a female-to-male ratio of 5-6:1. 2,6,8,9,11 Thus, it has been suggested that the disease is related to exogenous steroid hormones or gynecologic hormones, albeit studies have failed to show a definite connection. 1,3,6,9 Previous studies have shown that liver hemangiomas are usually smaller than 3 cm and 85% of lesions are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Hemangiomas are usually seen between the ages of 30-50 years, with a female-to-male ratio of 5-6:1. 2,6,8,9,11 Thus, it has been suggested that the disease is related to exogenous steroid hormones or gynecologic hormones, albeit studies have failed to show a definite connection. 1,3,6,9 Previous studies have shown that liver hemangiomas are usually smaller than 3 cm and 85% of lesions are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Despite there being a lack of consensus with regards to the classification of giant hemangiomas, Adam et al described hemangiomas larger than 4 cm as ''giant.'' [3][4][5]8,11 Studies have suggested that there is a strong correlation between hemangioma diameter and symptoms. Hemangiomas larger than 10 cm are nearly always symptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this asymptomatic character, the size of the haemangioma varies greatly when discovered. 3 Adam et al defined giant haemangiomas as >4cm in diameter. 4 Giant liver haemangiomas can present with abdominal pain, fullness, mass, and complications such as platelet consumption coagulopathy (Kasabach-Merritt syndrome) and intraperitoneal haemorrhage due to rupture.…”
mentioning
confidence: 99%
“…8,9 The most commonly reported complications of giant haemangiomas are rupture with intraperitoneal haemorrhage that is either traumatic or non-traumatic, consumption coagulopathy, Budd-Chiari syndrome and congestive heart failure. 3,10,11 Case History A 40-year-old woman presented to our hospital with right hypochondrial pain and fullness as well as severe pallor. Three years previously, she had one session of transcatheter arterial embolisation in a private clinic for a giant haemangioma involving the left hepatic lobe.…”
mentioning
confidence: 99%